Amplified Arctic Surface Warming and Sea Ice Loss Due to Phytoplankton and Colored Dissolved Material - Pefanis, Vasileios; Losa, Svetlana N.; Losch, Martin; Janout, Markus A.; Bracher, Astrid; 1 Department of Climate Sciences Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research Bremerhaven Germany (Geophysical Research Letters, 2020)
Optically active water constituents attenuate solar radiation and hence affect the vertical distribution of energy in the upper ocean. To understand their implications, we operate an ocean biogeochemical model coupled to a general circulation model with sea ice. Incorporating the effect of phytoplankton and colored dissolved organic matter (CDOM) on light attenuation in the model increases the sea surface temperature in summer and decreases sea ice concentration in the Arctic Ocean. Locally, the sea ice season is reduced by up to one month. CDOM drives a significant part of these changes, suggesting that an increase of this material will amplify the observed Arctic surface warming through its direct thermal effect. Indirectly, changing advective processes in the Nordic Seas may further intensify this effect. Our results emphasize the phytoplankton and CDOM feedbacks on the Arctic ocean and sea ice system and underline the need to consider these effects in future modeling studies to enhance their plausibility. Plain Language Summary: The amount of microalgae and colored dissolved organic material in the ocean determines how much light is absorbed in the surface waters and how much can reach greater depths. The vertical distribution of energy affects the upper ocean temperature and general circulation. Here, we use a numerical ocean model with biogeochemistry and sea ice, in which the individual effects of microalgae and colored dissolved organic matter can be turned on and off separately. When both effects are turned on, the summertime surface temperatures in the Arctic are larger and consequently more sea ice melts, so that the sea ice season is shorter by up to one month. We find that, to a large extent, the colored dissolved material is responsible for these changes. An increase of this material due to climate change will amplify the observed Arctic surface warming. For better projections of climate change, new models should account for the effect of these light‐absorbing water constituents. Key Points: ...